Exploring infant feeding practices: cross-sectional surveys of South Western Sydney, Singapore, and Ho Chi Minh City - Timothy Yong Qun Leow; Andrew Ung; Shelley Qian; Jessie Thanh Nguyen; Yvonne An; Poonam Mudgil; John Whitehall (BMC, 2017)
Abstract Background Infant feeding practices are known to influence the child's long-term health. Studies have associated obesity and other diseases with reduced breastfeeding and early introduction of high calorie beverages (HCBs). The rising prevalence of obesity is already a problem in most developed countries, especially Australia, but cultural differences are influential. Our aim is to examine and compare infant feeding practices and educational levels of respondents through questionnaires in three culturally different sites: Campbelltown (South Western Sydney), Australia, Singapore and Ho Chi Minh City, Vietnam (HCMC). Methods Consenting parents and carers (aged ≥18 years old) of at least one child (≤6 years old) were recruited from paediatric clinics in Campbelltown, Singapore and HCMC. Participants completed an infant feeding practices questionnaire regarding breastfeeding, beverage and solid initiation in addition to the parent's ethnicity, age, and educational level. Data was analysed quantitatively using SPSS. Results Two hundred eighty-three participants were recruited across the three sites, HCMC (n = 84), Campbelltown (n = 108), and Singapore (n = 91). 237 (82.6%) children were breastfed but in all only 100 (60.2%) were exclusively breastfed for five months or more. There was a statistical difference in rates of breast feeding between each region. HCMC (n = 18, 21.4%) had the lowest, followed by Campbelltown (n = 35, 32.4%), and then Singapore (n = 47, 51.7%). There was also a difference in rates of introduction of HCBs by 3 years of age, with those in HCMC (n = 71, 84.5%) were higher than Campbelltown (n = 71, 65.8%) and Singapore (n = 48, 52.8%). The educational level of respondents was lower in Vietnam where only 46.4% (n = 39) had completed post-secondary education, compared to 75.0% (n = 81) in Campbelltown and 75.8% (n = 69) in Singapore. Conclusions Rates of breast feeding were inversely correlated with rates of introduction of HCB and positively related to educational achievement. Vietnam had lowest rates of breast feeding, higher rates of introduction of HCBs, and lower rates of education. Given rising rates of obesity, there is a need for more effective programmes to promote breast feeding and restrict false advertising of HCBs.